2019
DOI: 10.3390/chemistry1010006
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Alcohols, Amines, Phenols, Thiols under Catalyst and Solvent-Free Conditions

Abstract: In the present study, an easy and an efficient approach is reported for the acetylation of alcohols, amines, phenols, and thiols under solvent- and catalyst-free conditions. The experimental conditions were milder than conventional methods and the reactions were completed in shorter reaction time. The examined substrates afforded higher yields of the acetylated products under the short reaction time. Comparison of this work with earlier reported procedures reveals that this method offers some advantages than w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 67 publications
0
12
0
1
Order By: Relevance
“…[22][23][24][25][26][27][28][29][30] Recently, Anbu et al have reported the solvent and catalyst free process for the acylation reaction. 31 But, all these reported processes are associated with a number of limitations such as longer reaction time, use of toxic solvents, high reaction temperature and ease of handling. Therefore, there is still a need for the development of new catalysts that can be used under mild reaction conditions to get the good yield of the acetylated products using green chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30] Recently, Anbu et al have reported the solvent and catalyst free process for the acylation reaction. 31 But, all these reported processes are associated with a number of limitations such as longer reaction time, use of toxic solvents, high reaction temperature and ease of handling. Therefore, there is still a need for the development of new catalysts that can be used under mild reaction conditions to get the good yield of the acetylated products using green chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…To date, acetylation with acyl halides or acid anhydrides has been reported using solvents and catalysts at room temperature or higher (>40 • C). Acetylation methods have been reported without catalysts at high solvent temperatures (60-70 • C) or with a variety of catalysts from room temperature to 110 • C [22]. With regard to PBDE molecules, only 11 has been obtained from acetylation using Ac 2 O with pyridine at room temperature for 24 h [23].…”
Section: Resultsmentioning
confidence: 99%
“…The reaction conditions depend on several factors including time of reaction and concentration of acetic anhydride that keeps varying to determine the optimum conditions for the acetylation. The concentration of acetic anhydride used for acetylation were 10 to 20% and 6gpl of zinc chloride as a catalyst at MLR of 1:10 and the time of reaction was 1-4hr at room temperature due to temperature effects tensile strength of the fabric [16,17]. The combination of glacial acetic acid at 1:2 ratios to sample weight used for acetylation method.…”
Section: Acetylation Processmentioning
confidence: 99%